Restaurant Customer Ordering System / Racheal Ebin Gon - Racheal, Ebin Gon (2003)
The project, which is to be undertaken, refers to the current restaurant system. Based on the current system, research and analysis is done to come up with a proposed system, which improves the business operations. The method used in this project will be Structured Systems Analysis and Design Method (SSADM), which is a standard approach to the task, techniques, and documentation of projects to be under taken. SSADM covers areas of analysis and the design solutions to major projects in an effective way of helping to understand how to apply computer techniques to the solution of problems where possible and to guide the project through testing, debugging and documentation phases until the final implementation phase has been achieved. By the use of this method, it is expected to help others understand the overall business environment especially in the restaurant business. This project highlights problems mainly in the area of the current customer ordering systems. Ways to improve this area will be the discussion in the documentation of this project. The overall project development must bring benefit and at a cost, which can be justified and agreed by the organization concerned. The system, which is to be developed, is the Restaurant Customer Ordering System (RCOS). The proposed system is intended to further improve business efficiency in the management and customer service. The overall idea of the proposed system came about after first hand experience and personnel observation of the current system which brought the idea to find ways to further improve the current system mainly concerning the customer service.